Managing Religious Diversity: An Ihsan Approach - Armayanto, Harda; Suntoro, Adib Fattah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
This study begins with the notion that some religious groups engage in intolerance and violence directed at members of their religious community and at people of other religions. This shatters interfaith relationships. In addition, religion is being accused to be the reason for intolerance and a source of conflict and chaos. Conversely, Islamic teachings can be used as approaches in managing religious communities and social interaction. An example is the concept of ihsan. The purpose of this study is to explain the concept of ihsan as an approach to fostering the interreligious relationship. This qualitative research used library research for data collection from books, journal articles, and documents related to the management of religious diversity and the concept of ihsan. The collected data were processed using descriptive analytics. With both methods, the researcher reports and presents the collected data to be analyzed and concluded. This research finally found that the concept of ihsan which contains ‘witnessing’ and ‘supervision’ is appropriate for use by Muslims as an approach to managing the plurality of religious communities. This is because Muslim, while always remaining steadfast in their faith, can still establish positive relationships with those who practice other religions using the ihsan approach.